STRATEGI PENGEMBANGAN OBJEK WISATA CEMORO SEWU DI KABUPATEN SELUMA - Hanila, Siti; Ferina, Zahra Indah (Jurnal Ekonomi Manajemen, 2020)
ABSTRACTBengkulu Province is one of the Tourism Destination Areas (DTW) of Indonesia in Sumatra. As a tourist destination. Cemoro Sewu attractions see the need to improve services to tourists, both in terms of improving the quality of human resources, as well as improving tourist facilities and infrastructure as an effort to attract tourists to visit. Transferring the status of tourist sites from nature reserves to natural tourism parks (TWA) will bring a positive impact on tourism in Seluma Regency. The purpose of this study is to study and analyze what internal and external factors support and hinder the development of Cemoro Sewu Tourism Obejek and determine how the development strategy will be. Data collection methods used are literature study methods and questionnaires by completing the questionnaire list to respondents. Sampling is done randomly or random sampling without regard to strata that are in the population, if members of the population are considered homogeneous. Assumptions of effective strategies to maximize the power and opportunities for enhancing tourism objects and opportunities and challenges. The analytical method used in this study is the SWOT (Strength, Weaknesses, Opportunity, Threats) analysis method. Data obtained from the results of the study will be analyzed the strengths, weaknesses, opportunities and risks of the application of marketing strategies in the context of developing Cemoro Sewu Tourism Objects. To determine future development strategy formulations, the combined marketing strategy formulations are approved through the SWOT matrix.Keywords: Cemoro Sewu tourism; development strategy.ABSTRAKProvinsi Bengkulu adalah salah satu Daerah Tujuan Wisata (DTW) Indonesia di Sumatera. Sebagai tujuan wisata. Objek wisata Cemoro Sewu melihat perlunya meningkatkan pelayanan kepada wisatawan, baik dari segi peningkatan kualitas sumber daya manusia, maupun peningkatan sarana dan prasarana wisata sebagai upaya menarik wisatawan untuk berkunjung. Memindahkan status lokasi wisata dari cagar alam ke taman wisata alam (TWA) akan membawa dampak positif bagi pariwisata di Kabupaten Seluma. Tujuan dari penelitian ini adalah untuk mempelajari dan menganalisis faktor internal dan eksternal apa yang mendukung dan menghambat pengembangan Wisata Cemoro Sewu Obejek dan menentukan bagaimana strategi pengembangan akan. Metode pengumpulan data yang digunakan adalah metode studi literatur dan kuesioner dengan melengkapi daftar kuesioner kepada responden. Pengambilan sampel dilakukan secara acak atau acak tanpa memperhatikan strata yang ada dalam populasi, jika anggota populasi dianggap homogen. Asumsi strategi yang efektif untuk memaksimalkan kekuatan dan peluang untuk meningkatkan objek dan peluang dan tantangan pariwisata. Metode analisis yang digunakan dalam penelitian ini adalah metode analisis SWOT (Strength, Weaknesses, Opportunity, Threats). Data yang diperoleh dari hasil penelitian akan dianalisis kekuatan, kelemahan, peluang dan risiko penerapan strategi pemasaran dalam konteks pengembangan Objek Wisata Cemoro Sewu. Untuk menentukan formulasi strategi pengembangan masa depan, formulasi strategi pemasaran gabungan disetujui melalui matriks SWOT.Kata Kunci: wisata Cemoro Sewu; strategi pengembangan.